Adhesive/dentin interface: The weak link in the composite restoration - Eslick, John; Bohaty, Brenda S.; Camarda, Kyle; Park, Jonggu; Wang, Yong; Singh, Viraj; Marangos, Orestes; Sene, Fabio; Katz, J. Lawrence; Ye, Qiang; Spencer, Paulette; Topp, Elizabeth M.; et al. (My University, 2010)
Results from clinical studies suggest that more than half of the 166 million dental restorations that were placed in the United States in 2005 were replacements for failed restorations. This emphasis on replacement therapy is expected to grow as dentists use composite as opposed to dental amalgam to restore moderate to large posterior lesions. Composite restorations have higher failure rates, more recurrent caries, and increased frequency of replacement as compared to amalgam. Penetration of bacterial enzymes, oral fluids, and bacteria into the crevices between the tooth and composite undermines the restoration and leads to recurrent decay and premature failure. Under in vivo conditions the bond formed at the adhesive/dentin interface can be the first defense against these noxious, damaging substances. The intent of this article is to review structural aspects of the clinical substrate that impact bond formation at the adhesive/dentin interface; to examine physico-chemical factors that affect the integrity and durability of the adhesive/ dentin interfacial bond; and to explore how these factors act synergistically with mechanical forces to undermine the composite restoration. The article will examine the various avenues that have been pursued to address these problems and it will explore how alterations in material chemistry could address the detrimental impact of physico-chemical stresses on the bond formed at the adhesive/dentin interface. © 2010 Biomedical Engineering Society.
Keywords: Adhesive development; Adhesive/dentin interfacial bond; Bonding durability; Physico-chemical stresses; Structure